THE EFFECT OF SHALAT MOVEMENT ON THE DOWN BACK FLEXIBILITY IN BOARDING SCHOOL STUDENTS - Fitria Febriana; Eka Febri Zulissetiana (International Islamic Medicine Forum, 2020)
Flexibility is one component of body fitness needed for daily activities, such as bending, running, and walking. Human flexibility significantly increases in childhood and reaches its peak in adolescence. One of the exercises related to increasing lower back flexibility is stretching exercise in the form of Islamic prayers five times a day. This study was conducted to know the effect of stretching exercise on lower back flexibility in students age 12-15 years. This research is analytical observational research with a cross-sectional design using proportionate stratified random sampling. The subject of the research is 70 students of the Islamic school and 70 students of public school in Kota Palembang. Lower back flexibility is measured by the Sit and Reach Test. The Mann-Whitney Test analyzed data. There is a significant difference between lower back flexibility of Islamic school that do stretching exercise and lower back flexibility of public school that does not include stretching exercise (p = 0,000). Stretching exercise in the form of Islamic prayer increases lower back flexibility.